PILLARS OF COMPETITIVENESS AS FDI DETERMINANTS IN HOST COUNTRIES: A REVIEW OF THE PANEL DATA EMPIRICAL STUDIES - Stankov, Biljana; Roganović, Milijana; Damnjanović, Jelena (International Journal of Economic Practice and Policy, 2019)
In the scientific literature competitiveness has been claimed to be of one of the determinants of FDI inflows, since it has been associated with high standard of living, cost reduction, quality standards, improvement of business processes, efficiency, and so on. Studies regarding the correlation between competitiveness and FDI inflows are scarce in the literature mainly due to the lack of a universally accepted definition of competitiveness (Criste, Mosneanu and Glod, 2008). In the emerging and developing countries national competitiveness has certainly been a very important determinant of FDI inflows, but it has also been a significant factor in developed countries. If a country is more competitive in comparison to the others, especially the ones in its immediate surrounding or the ones which are in many ways similar to it, its investment environment becomes more attractive for foreign investors. In such circumstances, FDI inflows are expected to intensify and thus stimulate economic growth and development. Competitiveness affects the achieved level of productivity in the country, and directly determines the level of social well-being. On the other hand, FDI is often seen in scientific literature as a source of competitiveness, since it secures transfer of technology and knowledge from home to host countries through capital flows.
Keywords: FDI determinants; panel data analysis; host country; foreign direct investment